Effect of the strain Bacillus amyloliquefaciens FZB42 on the microbial community in the rhizosphere of lettuce under field conditions analyzed by whole metagenome sequencing - Kröber, Magdalena; Wibberg, Daniel; Grosch, Rita; Eikmeyer, Felix; Verwaaijen, Bart; Chowdhury, Soumitra P.; Hartmann, Anton; Pühler, Alfred; Schlüter, Andreas (Frontiers in Microbiology, 2014)
Application of the plant associated bacterium Bacillus amyloliquefaciens FZB42 on lettuce (Lactuca sativa) confirmed its capability to promote plant growth and health by reducing disease severity (DS) caused by the phytopathogenic fungus Rhizoctonia solani. Therefore this strain is commercially applied as an eco-friendly plant protective agent. It is able to produce cyclic lipopeptides (CLP) and polyketides featuring antifungal and antibacterial properties. Production of these secondary metabolites led to the question of a possible impact of strain FZB42 on the composition of microbial rhizosphere communities after its application. Rating of DS and lettuce growth during a field trial confirmed the positive impact of strain FZB42 on the health of the host plant. To verify B. amyloliquefaciens as an environmentally compatible plant protective agent, its effect on the indigenous rhizosphere community was analyzed by metagenome sequencing. Rhizosphere microbial communities of lettuce treated with B. amyloliquefaciens FZB42 and non-treated plants were profiled by high-throughput metagenome sequencing of whole community DNA. Fragment recruitments of metagenome sequence reads on the genome sequence of B. amyloliquefaciens FZB42 proved the presence of the strain in the rhizosphere over 5 weeks of the field trial. Comparison of taxonomic community profiles only revealed marginal changes after application of strain FZB42. The orders Burkholderiales, Actinomycetales and Rhizobiales were most abundant in all samples. Depending on plant age a general shift within the composition of the microbial communities that was independent of the application of strain FZB42 was observed. In addition to the taxonomic profiling, functional analysis of annotated sequences revealed no major differences between samples regarding application of the inoculant strain.